Effect of long time whole-body vibration training on muscle function and postural balance - Kang, Seung-Rok; Yu, Chang-Ho; Moon, Dong-An; Kwon, Tea-Kyu (International journal of precision engineering and manufacturing, 2014)
This study intended to identify the effect of the long time whole body vibration exercise on the muscle function and postural balance. The twenties subjects in young people were recruited, and they were classified into WBV and Non-WBV groups. The vibration exercise was conducted 30 minutes a day for 4 days a week for a total 8 weeks, and the vibration protocol were 25Hz frequency and 5mm amplitude. To verify the muscle function according to the long time vibration exercise, the isokinetic muscle function of the knee joint torque was evaluated, while the total work of maximal peak torque to evaluate the enhancement effect of muscular strength, as well as the average power, angle to peak torque, and acceleration time to evaluate the muscular reaction, was analyzed. Also, changes in COP were measured and analyzed to research the functional change of the postural balance. As a result of the experiment, the Non-WBV group did not show changes in the muscular function and postural balance function, while the WBV group showed increased muscular function by 29.11%(maximal peak torque: 17.91%, total work: 26.78%, average power: 39.11%, angle to peak torque: 25.21%, acceleration time: 36.51%), and increased postural balance function by 64.76%.